Systematic review of creativity didactic tools and resources developed in spanish - González Moreno, Alba (2021)
Introduction: Creativity is a capacity that is present in all human beings and that is characterized by generating original solutions to a certain conflict. Objective: This systematic review aims to identify both the instruments to measure creativity and the different resources that can be used to improve it in Spanish. Method: For this, two searches have been carried out: one for instruments and another for resources in the Web of Science, Scopus, Dialnet Plus and Ebsco databases using certain search formulas, from which a total of 34 studies have been obtained from among both searches. Results: The results show a diversity of instruments and resources, techniques or activities existing in the Spanish language with which creativity can be enhanced. Discussion: This work can help other researches to identify which instruments or resources are best adapted to their studies to be carried out.